Defining the Ideal Lumbar Total Disc Replacement Patient and Standard of Care. (15th December 2017) - Gornet, Matthew; Buttermann, Glenn; Guyer, Richard; Yue, James; Ferko, Nicole; Hollmann, Sarah
Abstract : N/A: Lumbar total disc replacement, now in use since 2004, was determined by the panel to be a standard of care for the treatment of symptomatic single-level lumbar degenerative disc disease in the active patient subpopulation as outlined by the investigational device exemption study criteria. The large body of evidence supporting this statement, including surgeons' experiences, was presented and discussed. Consensus statements focusing on decision-making criteria reflected that efficacy, long-term safety, clinical outcomes with validated measures, and cost-effectiveness should form the basis of decision-making by payers. Diagnostic challenges with lumbar degenerative disc disease patients were discussed among the panel, and it was concluded that although variably used among surgeons, reliable tools exist to appropriately diagnose discogenic back pain.